Natural suspended particulate matter (SPM) versus lab-controlled particles: Comparison of the reactivity and association mode of Zn. (May 2022) - Le Meur, Mathieu; Montarges-Pelletier, Emmanuelle; Gley, Renaud; Briois, Valérie; Michot, Laurent; Kanbar, Hussein; Caillet, Céline; Razafitianamaharavo, Angelina; Villieras, Frédéric
Abstract: River suspended particulate matter (SPM) plays a crucial role in the fate and behavior of pollutants such as Zn, a widespread trace metal commonly encountered in continental surface waters. SPM comprises particles and colloids and is described as complex, heterogeneous particles composed of mineral, organic and microbiological components with high surface reactivity. In this study, the surface properties of river SPM and its capacity to bind Zn were probed using electrophoretic mobility (EM) experiments, specific surface area (SSA) measurements, Zn adsorption tests and X-ray absorption spectroscopy (XAS). The external characteristics and reactivity of lab-controlled mineral phases (illite, ferrihydrite, illite-iron (hydr)oxide composite, and calcite) were investigated as for natural SPM. The electrophoretic mobility (EM) of the SPM exhibited low variations among the samples and was essentially assigned to the clay particles that dominate the mineralogical composition. Except for two samples, Zn adsorption experiments evidenced comparable adsorption capacity in relation to their different mineral and chemical compositions. Zn K-edge XAS data revealed that at low Zn loadings, the binding mode of this metal with environmental particles was controlled by its mineralogical composition. Indeed, linear combination fitting of the XAS curves, completed by shell-to-shell fitting, revealed that Zn is associated with SPM by surface complexation. The XAS results showed that for SPM samples collected in the high flow regime, Zn was mainly bound to clay minerals. In contrast, for the SPM sample collected during the low flow regime, Zn was bound not only to clay minerals but also to iron (hydr)oxides. Highlights: External properties of river suspended particles were not completely predicted by organic matter and clay mineral contents. Zn adsorption was far much higher for river samples than for pure minerals. Zn binding mode was evidenced by X-ray spectroscopic data. Pure minerals can hardly mimic the properties of environmental particles.